Kajian Penerjemahan Berbasis Korpus: Paradigma Baru dalam Penelitian tentang Penerjemahan - Yuliawati, Susi (Kementerian Sekretariat Negara Republik Indonesia, 2018)
Corpus linguistics has given a significant impact to various kinds of research which studies language, including translation studies. The impact of corpus linguistics to the development of translation studies is marked by the availability of corpora that allow us to study translation as empirical phenomenon and the emergence of corpus-based translation studies. The present paper explores several key concepts in corpus-based translation studies, resulted from the marriage of corpus linguistics and descriptive translation studies. Techniques and methods developed by corpus linguistics are thought to have the capability of extending the scope of translation research and introduce new pattern of thought for translation researchers. For that reason, the present paper discusses the paradigm shifts in translation studies; types of corpora and corpus analysis techniques applied for translation studies; and the development of corpus-based translation studies. The paper is expected to inspire experts in the fields of translation studies as well as corpus linguistics, particularly in Indonesia, to collaborate in developing corpus-based translation studies, which hitherto apparently has not been explored yet. Keywords: corpus linguistics, translation studies, corpus-based translation studies, descriptive translation studies.